Factors Related to the Incident of Postpartum Blues - Rika Ruspita; Rifa Rahmi; Komaria Susanti (Jurnal Bidan Cerdas, 2026)
Background: The incidence of postpartum blues varies, with Asia being a country that also experiences a fairly high incidence of postpartum blues, ranging from 26-85%, such as in Japan at 15-50%. Meanwhile, the United States 27%, France 31.7%, Nigeria 31.3% and Greece 44.5%. In Indonesia, several studies have been conducted on postpartum blues, including one in Riau Province, specifically in the city of Pekanbaru, where approximately 16.7% of postpartum mothers experience postpartum blues. This study aimed to determine the relationship between husband's support, attitudes and knowledge towards postpartum blues in the Independent Practice of Midwife Rosita Pekanbaru. Method: Using quantitative with analytical descriptive design. The location of this research was carried out at the Pekanbaru Midwife Rosita Maternity Home in April 2021 for 4 months. The sample in the Total Sampling research was all postpartum mothers at the Independent Practice of Midwife Rosita Pekanbaru totaling 30 people, the independent variables were husband's support, attitude, knowledge while the dependent variable was postpartum blues. Results: There is a relationship between husband's support (p=0.004), attitude (p=0.007) and knowledge (p=0.000) regarding postpartum blues. Conclusion: There is a relationship between husband's support, attitudes, knowledge and postpartum blues. This research suggests that health workers need to provide education to postpartum mothers and husbands about postpartum blues so that husbands are aware that their wives really need them at certain times and that husbands are expected to be there when their wives need them.